THE INFLUENCE OF TIKTOK ON THE DECLINE OF ADOLESCENT MORALITY: A Study on Students of IAIN Madura - Ibrohim .; Maulida Laila Ramadhani; Siti Mariyam (Indonesian Journal of Islamic Communication, 2023)
As technology develops, Tiktok has become an application that is in great demand by people of all walks of life, especially teenagers. Indonesia is the 4th largest user in the world. This application provides various kinds of short videos such as funny videos, about education, motivation and so on. The duration of using Tiktok exceeds the duration of other social media users such as Facebook, Instagram, Twitter and so on. The purpose of this study, the first to determine the effect of Tiktok on the low morality of adolescents at IAIN Madura, the second to find out how to overcome these problems. The research method used is a qualitative method, because the data from this research are included in descriptive form. The results of this study indicate that Tiktok is very influential on the low morale of IAIN Madura teenagers, namely the fading of etiquette in dressing, as well as the deterioration of the morals and morals of teenagers. The solution is to have self-awareness, limit the time to use Tiktok, increase religious knowledge and finally have parental supervision. Tiktok not only contains bad things, good things are also available in it, but dominant teenagers get the negative influence.